Preserved heart function after left ventricular pressure overload in adult mice subjected to neonatal cardiac hypoplasia. (24th July 2017) - Heinecke, K.; Heuser, A.; Blaschke, F.; Jux, C.; Thierfelder, L.; Drenckhahn, J.-D.
Abstract : Intrauterine growth restriction in animal models reduces heart size and cardiomyocyte number at birth. Such incomplete cardiomyocyte endowment is believed to increase susceptibility toward cardiovascular disease in adulthood, a phenomenon referred to as developmental programming. We have previously described a mouse model of impaired myocardial development leading to a 25% reduction of cardiomyocyte number in neonates. This study investigated the response of these hypoplastic hearts to pressure overload in adulthood, applied by abdominal aortic constriction (AAC). Echocardiography revealed a similar hypertrophic response in hypoplastic hearts compared with controls over the first 2 weeks. Subsequently, control mice develop mild left ventricular (LV) dilation, wall thinning and contractile dysfunction 4 weeks after AAC, whereas hypoplastic hearts fully maintain LV dimensions, wall thickness and contractility. At the cellular level, controls exhibit increased cardiomyocyte cross-sectional area after 4 weeks pressure overload compared with sham operated animals, but this hypertrophic response is markedly attenuated in hypoplastic hearts. AAC mediated induction of fibrosis, apoptosis or cell cycle activity was not different between groups. Expression of fetal genes, indicative of pathological conditions, was similar in hypoplastic and control hearts after AAC. Among various signaling pathways involved in cardiac hypertrophy, pressure overload induces p38 MAP-kinase activity in hypoplastic hearts but not controls compared with the respective sham operated animals. In summary, based on the mouse model used in this study, our data indicates that adult hearts after neonatal cardiac hypoplasia show an altered growth response to pressure overload, eventually resulting in better functional outcome compared with controls.